The evaluation of secondary metabolites in Saccharum officinarum L. and Mimosa invisa Mart. as natural herbicides - Roeswitawati, Dyah; Hussain, Zahid; Jan, Asad; Zekker, Ivar; Mel, Maizirwan; Setyobud, Roy Hendroko; Muhidin, Muhidin; Hudin, Davit (Deanship of Scientific Research, The Hashemite University, Jordan, 2022)
The giant sensitive plant (Mimosa invisa Mart.) is a major weed found in the sugarcane (Saccharum officinarum L.) farming areas, which dominates and adversely affects the quantity and quality of the harvest. This weed poses a threat to both the sugarcane farmers and sugar companies because it causes about a 6 % to 9 % decline in the plant’s biomass and a 0.09 % reduction in the crop yield. M. invisa has great competitiveness against the crop plant S. officinarum and also an increased population efficiency of 14.08 % in the first year (plant cane) to 38.55 % in the third year (3rd ratoon). Therefore, this research aims to determine the metabolic compounds in the rhizosphere of M. invisa and S. officinarum and assess their roles as allelochemicals. Research was conducted at the Laboratory of Agrotechnology, Faculty of Agriculture and Animal Science, University of Muhamadiyah Malang, and Central Laboratory of the Indonesian Legume and Tuber Crops Research Institute, Malang. The field research was carried out in the Research Garden Krebet Baru Sugar Factory, Malang, East Java, Indonesia. The descriptive qualitative research design was used and data were arranged randomly in groups of three treatments and three replications. The treatment details were planted in different plots of land each as, T1: Mimosa invisa only, T2: Mimosa invisa mixed Saccharum officinarum, and T3: Saccharum officinarum only. Furthermore, the analysis of metabolic compounds, using the Gass Cromatografy Mass Spectromotometry (GCMS), showed the presence of octadecanoic acid (an allelochemical compound) and methyl ester (2.06 %) in the rhizosphere of M. invisa and S. officinarum. These metabolite compounds are commonly used as herbicide activators.